Violência intrafamiliar contra idosos : estudo do contexto de Carazinho-RS - Costa, Leandra Sodréia Tesser da (2011)
The increase contingent elderly determines that aging is permeated by an extended family get-together. This convivial often develops so contentious, determining the occurrence of domestic violence. Through this finding were strokes search objectives: identify how the domestic violence against older persons in the municipality of Carazinho-RS; know the profile of older people suffering domestic violence; know the profile of the perpetrator; identify the types of violence experienced by the elderly at home; identify who is the guy who makes the complaint; check which forwards data complaints of violence and the outcome of proceedings in the District of Carazinho-RS. It is a retrospective documentary study of type series of cases, with a quantitative approach. After the approval of the Ethics Committee of UPF, the data were collected from police reports on domestic violence against the elderly in 2006, the precinct of Carazinho-RS. And to check the outcome of the complaint held were considered surveys and processes in the Forum of that municipality. The data were analyzed through descriptive statistics. It was found that the majority of the elderly who suffer domestic violence is female, retired, ranging in age between 60 and 70 years old, married and low schooling. The aggressor is males aged 60 years, most married with low schooling and retired; the companions, sons, daughters-in-law and sons-in-law are primarily responsible for the violence. The elderly makes the complaint itself, being the most common type of violence is the physical, psychological, then the main reason the family conflicts. Of the 55 police reports, there were six processes with agreement between the parties and 22 archives for non-attendance of the victim. Four cases were handled with protective measure and process the elder died before resolution, filed for lack of evidence